PENGARUH BELANJA DAERAH DAN PEMBANGUNAN INFRASTRUKTUR TERHADAP PERTUMBUHAN EKONOMI DAN KESEJAHTERAAN MASYARAKAT KABUPATEN/KOTA PROVINSI BALI - Dewi, Ni Wayan Diah Mia Kusuma; Dewi, Made Heny Urmila (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 10 No 1 (2021): VOL 10 NO 1, JANUARI 2021 [ 1 - 450 ], 2021)
Community welfare one of goals epected each region, including districts / cities in Bali Province. One of the efforts made by the government to improve people's welfare is development efforts. Success of economic development is strongly supported by regional revenues and infrastructure. The purpose  this study; (1) analyze the effect of regional spending and infrastructure development on economic growth in the Regency / City Bali Province; (2) analyze the effect of regional spending and infrastructure development on the welfare of the community in the Regency / City Bali Province; (3) analyze economic growth as a mediating variable effect of regional spending and infrastructure development on people's welfare. Data used are secondary data, total 81 observations. Analysis technique used path analysis. The results showed 1) regional spending and infrastructure directly have positive effect on economic growth in regencies / cities of Bali Province; 2) regional spending and economic growth have significant positive effect on people's welfare, while infrastructure haven’t positive effect on people's welfare, 3) economic growth not a mediating variable for the effect of regional spending on the welfare of the people in the regencies / cities of Bali Province.   Keywords: community welfare, economic growth, regional spending, infrastructure, path analysis.